Designing an Ergonomic Elderly Trolley to Improve Hypermarket Competitiveness: an Indonesian Perspective - Wirawan, Christina; Sarvia, Elty; Widjaja, Jahja Hamdani; Martin, Martin (Universitas Kristen Maranatha, 2024)
Owing to physical constraints, elderly individuals frequently have trouble shopping at hypermarkets. To address this issue, this study builds a trolley to assist the elderly in shopping comfortably. Furthermore, this design provides a hypermarket with distinct and competitive advantages in terms of increasing customer traffic. This study employs both qualitative and quantitative approaches. Soft System Methodology was utilized to conceptualize the problem qualitatively, while quality function deployment and morphological diagrams were employed to process quantitative data. The result of this study was an elderly trolley design. The trolley is designed based on anthropometric data of the elderly. The shape of the trolley is not much different from a regular trolley but is equipped with a powered component so that it can be driven, a raised seat, and a foldable basket. Payment service support for the designed trolley has also been developed. With the design of the trolley and payment services for the elderly, it is expected that the elderly will be more comfortable shopping and increase the competitiveness of hypermarkets.